2008
DOI: 10.1038/ng.168
|View full text |Cite
|
Sign up to set email alerts
|

Conservation of the H19 noncoding RNA and H19-IGF2 imprinting mechanism in therians

Abstract: Comparisons between eutherians and marsupials suggest limited conservation of the molecular mechanisms that control genomic imprinting in mammals. We have studied the evolution of the imprinted IGF2-H19 locus in therians. Although marsupial orthologs of protein-coding exons were easily identified, the use of evolutionarily conserved regions and low-stringency Bl2seq comparisons was required to delineate a candidate H19 noncoding RNA sequence. The therian H19 orthologs show miR-675 and exon structure conservati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
166
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(175 citation statements)
references
References 50 publications
4
166
0
2
Order By: Relevance
“…Comparative genome studies have revealed extensive conservation of H19/Igf2 in therians (6). Consistently, key features of imprinting, as well as spatial organization of the mouse and human loci, are shared, including DNA methylation patterns, CTCF-binding sites (CTSs), and cis-regulatory elements.…”
mentioning
confidence: 84%
“…Comparative genome studies have revealed extensive conservation of H19/Igf2 in therians (6). Consistently, key features of imprinting, as well as spatial organization of the mouse and human loci, are shared, including DNA methylation patterns, CTCF-binding sites (CTSs), and cis-regulatory elements.…”
mentioning
confidence: 84%
“…mechanism apart from imprinting regulation. 7,8 However, the detailed mechanism by which H19 performs its regulatory function via miR-675 on target genes has not been clarified.…”
Section: Introductionmentioning
confidence: 99%
“…Ceci suggère un déploiement spéci-fique des ICR chez les euthériens ou, alternativement, l'utilisation par les marsupiaux d'un mode de régulation indépendant de la méthylation. Le consortium SAVOIR (sequence analysis of vertebrate orthologous imprinted regions) a entrepris depuis plusieurs années l'analyse comparative systématique chez le poulet, le wallaby/kangourou et l'ornithorynque des régions orthologues des locus soumis à empreinte connus [21]. La publication récente de la séquence du génome de l'ornithorynque a facilité l'identification des régions synténiques et des éléments fonctionnels importants, en relation avec l'évolution des génomes [22].…”
Section: Coévolution De L'empreinte Parentale Avec L'expansion Des Trunclassified